Comparative Study of Angiotensin Convertase Enzyme (ACE2) Gene Expression in Patients with Covid-19 By Molecular Method - Behrooz Farzanegan; Naghmeh Bahrami; Mohammad Fathi; Saba Tahmasebi; Mehdi Kazem Pour Dizaji; Shadi Shafaghi; Farnaz Ahmadi; Farnoush Mohammadi; Seyedeh Zahra Fotook Kiaei; Mona Mohajeri Tehrani; Masoume Farhangiyan; Abdolreza Mohamadnia (Journal of Craniomaxillofacial Research)
Introduction: The Covid 19 illness is triggered by a coronavirus known as SARS CoV-2. This particular virus spreads rapidly likely because of the Spike proteins affinity, to the human ACE2 cell receptor causing harm to organs, like the lungs in type 2 pneumocytes that abundantly express this receptor. Materials and Methods: The research methodology used in this study involved a case control approach. Patients were referred by a specialist following diagnosis. A total of 50 samples, from infectious cases and 50 samples from cases, with mild symptoms were analyzed for statistical purposes. The ACE2 gene expression was assessed using the Realtime RCR method after RNA extraction. Results: The findings indicate that the average age does not have an impact on individuals experiencing mild symptoms. Moreover, there is a decrease in the expression of ACE2 genes in the blood of patients with severe symptoms hospitalized in intensive care units as compared to those, with mild symptoms, highlighting a substantial disparity. Conclusion: The numerical value of fold change for ACE2 gene in severe type patients shows a decrease compared to mild patients and it is 2.11 times lower in severe type patients than mild type. Keywords: COVID-19; ACE2; Realtime RCR.